Foreword - Kharchenko, V.V.; Li, Z.M.; Liu, F.; Khotsyanovskii, A.O. (Проблемы прочности, 2014)
This issue of the journal contains papers selected from contributions, presented during the Second Global Annual Conference on Materials Science and Engineering (CMSE2013), which was held in Xianning, Hubei, China, November 20–22, 2013.